Ultraflexible sensor development via 4D printing: enhanced sensitivity to strain, temperature, and magnetic fields - Hou, Yanbei (2025)
This paper addresses the trade-off between sensitivity and sensing range in strain sensors, while introducing additional functionalities through an innovative 4D printing approach. The resulting ultraflexible sensor integrates carbon nanotubes/liquid metal hybrids and iron powders within an Ecoflex matrix. The optimization of this composition enables the creation of an uncured resin ideal for Direct Ink Writing (DIW) and a cured sensor with exceptional electromechanical, thermal, and magnetic performance. Notably, the sensor achieves a wide linear strain range of 350% and maintains a stable Gauge Factor of 19.8, offering an ultralow detection limit of 0.1% strain and a rapid 83-ms response time. Beyond superior strain sensing capabilities, the sensor exhibits outstanding thermal endurance for temperatures exceeding 300 °C, enhanced thermal conductivity, and a consistent resistance-temperature relationship, making it well-suited for high-temperature applications. Moreover, the inclusion of iron particles provides magnetic responsiveness, enabling synergistic applications in location and speed detection, particularly in home care. Leveraging DIW facilitates the creation of complex-shaped sensors with multiple functional materials, significantly broadening the sensor's capabilities. This convergence of additive manufacturing and multifunctional materials marks a transformative step in advancing the performance of next-generation sensors across diverse domains.